Impact of Selected Small-Molecule Kinase Inhibitors on Lipid Membranes - Meike Luck; Markus Fischer; Maximilian Werle; Holger A. Scheidt; Peter Müller (MDPI AG, 2021)
Small-molecule protein kinase inhibitors are used for the treatment of various diseases. Although their effect(s) on the respective kinase are generally quite well understood, surprisingly, their interaction with membranes is only barely investigated; even though these drugs necessarily come into contact with the plasma and intracellular membranes. Using biophysical methods such as NMR, ESR, and fluorescence spectroscopy in combination with lipid vesicles, we studied the membrane interaction of the kinase inhibitors sunitinib, erlotinib, idelalisib, and lenvatinib; these drugs are characterized by medium log p values, a parameter reflecting the overall hydrophobicity of the molecules, which is one important parameter to predict the interaction with lipid membranes. While all four molecules tend to embed in a similar region of the lipid membrane, their presence has different impacts on membrane structure and dynamics. Most notably, sunitinib, exhibiting the lowest log p value of the four inhibitors, effectively influences membrane integrity, while the others do not. This shows that the estimation of the effect of drug molecules on lipid membranes can be rather complex. In this context, experimental studies on lipid membranes are necessary to (i) identify drugs that may disturb membranes and (ii) characterize drug-membrane interactions on a molecular level. Such knowledge is important for understanding the efficacy and potential side effects of respective drugs.